Peer Supportive Group Therapy Dapat Meningkatkan Kualitas Hidup Anak dengan Thalasemia Beta Mayor di RS PMI Bogor - Nieniek Ritianingsih Ritianingsih; Yuliastati . (Poltekkes Kemenkes Bandung, 2014)
Thalasemia, peer suportive group therapy, kualitas hidup. ABSTRACT Thalassemia is hemolytic anemia disease inherited autosomal recessive caused by mutation of a single gene due to impaired formation of alpha or beta globin chains. Chronic disease state and effect of treatment which experienced by children with thalassemia can significantly affect the quality of life include the child's physical, emotional, social and school functioning . Quality of life of children with thalassemia can be improved with supportive peer group therapy . This study aimed to identify the effect of a supportive peer group therapy on quality of life of children with beta thalassemia major in PMI hospital in Bogor. This study is quantitative research using quasi experimental with pretest - post-test control group design. Thirty six respondents participated in this study for the following peer group supportive therapy for 8 weeks . Child's quality of life were evaluated before and after the activity. The results showed that peer group supportive therapy significantly improve the quality of life for children in beta thalassemia major( p < 0.05).